(untitled) (Junior Management Science, 2018)
Motivated by a lack in the current literature, this thesis reviews academic research on the economic and noneconomic goals of family firms. Heretofore, no detailed overview of different goals embedded in the goal setting-, outcome-, and alignment process has been provided. Using a systematic literature search and review process, I identify 117 relevant studies in the fields of management, economics, and affiliated domains between 1963 and 2018. Beyond a more detailed overview of the current state of research, I outline goal setting, outcomes, alignment, and four different family firm goal classes. Lastly, I show avenues for future research in the family firm–goal field. Motivated by a lack in the current literature, this thesis reviews academic research on the economic and noneconomic goals of family firms. Heretofore, no detailed overview of different goals embedded in the goal setting-, outcome-, and alignment process has been provided. Using a systematic literature search and review process, I identify 117 relevant studies in the fields of management, economics, and affiliated domains between 1963 and 2018. Beyond a more detailed overview of the current state of research, I outline goal setting, outcomes, alignment, and four different family firm goal classes. Lastly, I show avenues for future research in the family firm–goal field. Keywords: Family firms, economic goals, non-economic goals, socioemotional wealth